Development of a Scale to Address the Acceptance and Use of Online Social Networking Sites for Instructional Purposes - Elif Buğra Kuzu Demir, Yavuz Akbulut (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The current study aimed to develop a scale to address the acceptance and use of online social networking sites (SNSs) for instructional purposes among information technology teachers. The theoretical framework of the scale was based on The Unified Theory of Acceptance and Use of Technology (UTAUT). Data were collected from computer education departments of three state universities to conduct an exploratory factor analysis (n: 302) followed by a confirmatory factor analysis (n: 210). Analyses revealed a four-factor structure which sheltered 36 items. It was observed that acceptance and use of SNSs for instructional purposes were composed of performance expectancy, effort expectancy, social influence and behavioral intention, which explained 67.02 percent of the total variance with a high internal consistency coefficient (α=.97). The confirmatory analysis on the four-factor structure revealed acceptable fit indices as well (RMSEA= 0.075; SRMR=0.080; NNFI= .094; CFI= .094; α=.93). Higher scores from the scale can be interpreted as higher acceptance rate and tendency to use SNSs for instructional purposes.